Evaluation Of The Leave And Bud Decoctions Pinus Halepensis Mill Effects On The Induced-phenol Renal Toxicity In Wistar Rats - Berroukche, A .; Amara, S.; Halimi, S.; Benyamina, F. (University of Eloued جامعة الوادي, 2014)
Pinus halepensis M. (Pinaceae) has done object many indications in traditional medicine. Several studies have demonstrated a protective activity of essential oils extracted from various plant species against renal toxicity induced by chemicals in the animal model. The objective of this study is to assess the anti toxic effects of decocted leaves and buds of Pinus halepensis M. on Wistar rats initially exposed to phenol C6H5OH (180 mg / kg body weight). The results of laboratory analyzes of biochemical parameters revealed that decocted leaves and buds (250 mg / kg body weight) have shown a highly significant antitoxic activity (p < 0,001). The protective effect of decocted leaves and buds were respectively expressed by a decrease in serum concentrations of biochemical markers urea ( 0,32 and 0,28 g/l) and creatinine ( 121 & 13,8 g / l ) and electrolyte Calcium ( 89,8 & 109,5 g / l ) , Potassium ( 7 & 6,6 g / l ) and Sodium ( 130,5 & 129,6 g / l ).
Articale in Journal of fundamental and Applied Sciences Vol. 06 N. 02
Keywords: Pinus halepensis; Renal toxicity; Decocted leaves; Phenol.